Effect of 3-week exercise taper on the interval run performance of female hockey athletes - Liang, L.; Yan, Q. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The performance of an interval shuttle run is one of the most important performances for field hockey athletes because it is the main exercise form in the hockey match. This study was designed to research the effect of a 3-week taper on intermittent running performance. It will be instructive for coaches to optimize training methods.